Exploring the association between grandparental care and child development: Evidence from China. (30th March 2022) - Li, Hua; Hiilamo, Heikki; Zhu, Yidan Daisy; Lin, Ka
Abstract: Grandparental care has become an involuntary choice in life for many families, mainly due to parents' unavailability to provide care and the lack of public or affordable private childcare. This phenomenon has raised concerns regarding the effects of grandparental care along the dimensions of child development. This study aims to test the association between grandparental care and child development in three dimensions: subjective wellbeing, behavioural traits and study performance. It used data from the 2018 China Family Panel Studies survey. First, the study outlines the data and the applied method with defined variables, on the basis of which an overview on the current stage of grandparental care is presented. It then examines the association of the impact of grandparental care in different dimensions using the general linear model, along with the other influencing factors. Finally, a cross‐age group comparison is employed. The results of the study illustrate the difficulty of examining an overall picture of grandparental childcare, with its negative or positive associations. However, when evaluated using the features of different age groups of children's development, significant associations between grandparental care and child development are mainly found in the 6–11 age group, but the significant associations weaken or disappear in the 12–16 age group. Attachment theory and peer group theory are used to explain the difference between the two age groups.